2019
DOI: 10.36226/jrmb.v4i1.247
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Profitabilitas Bank BPR Di Provinsi Jawa Barat

Abstract: This study aims to estimate the effect of CAR, LDR, BOPO, and NPL on profitability (ROA) in rural banks in West Java Province for the period of 2012-2016. Data was collected from secondary data and data analysis using multiple linear regression. The results showed that: only BOPO proved to have a negative and significant effect on ROA. While other variables, namely CAR and NPL have a positive but not significant effect, and NPL has a negative effect but not significant to ROA. The results of the study provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
2
5
0
1
Order By: Relevance
“…This shows that the company uses a lot of third-party funds to finance current assets, while its current assets are more widely used to make a profit for the company. This is in line with research conducted by Asfali [3], Kurniasih et al [14], Mappadang, et al [15], Novica dan Yuniarwati [16], dan Okrianesia, et al [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This shows that the company uses a lot of third-party funds to finance current assets, while its current assets are more widely used to make a profit for the company. This is in line with research conducted by Asfali [3], Kurniasih et al [14], Mappadang, et al [15], Novica dan Yuniarwati [16], dan Okrianesia, et al [17].…”
Section: Discussionsupporting
confidence: 90%
“…These assets if managed properly will be a strength for the company. Companies with good asset management will tend to be able to overcome financial problems such as paying off shortterm debt and long-term debt [15].…”
Section: Firm Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini mengungkapkan proses profitabilitas Perusahaan akan meningkat dengan proses perputaran aset yang dilakukan secara efisien. Meningkatnya penjualan yang dilakukan oleh manajemen aset suatu bisnis usaha maka akan menaikkan rasio aktivitas (Mappadang et al, 2019). Di sisi lain, rasio ini bermanfaat dalam memberi nilai kapabilitas Perusahaan dalam mengoperasikan aktivitas hariannya.…”
Section: Rasio Aktivitasunclassified
“…Liquidity measures a company's capacity to fulfil its short-term debts by utilizing its current assets [4]. Previous research found that liquidity had a significant effect on financial distress [5][6][7][8][9][10][11]. However, the research conducted by [4], [12][13] find that liquidity has an insignificant effect on financial distress.…”
Section: Introductionmentioning
confidence: 99%